2017
DOI: 10.1371/journal.pntd.0005832
|View full text |Cite
|
Sign up to set email alerts
|

Larrea tridentata: A novel source for anti-parasitic agents active against Entamoeba histolytica, Giardia lamblia and Naegleria fowleri

Abstract: Protozoan parasites infect and kill millions of people worldwide every year, particularly in developing countries where access to clean fresh water is limited. Among the most common are intestinal parasites, including Giardia lamblia and Entamoeba histolytica. These parasites wreak havoc on the epithelium lining the small intestines (G. lamblia) and colon (E. histolytica) causing giardiasis and amebiasis, respectively. In addition, there are less common but far more deadly pathogens such as Naegleria fowleri t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 66 publications
0
21
0
4
Order By: Relevance
“…In intestinal protozoa (Giardia lambia, Entamoeba histolytica and Naeglia fowleri) of considerable pathogenicity to humans, secondary metabolites of creosote matter were shown to be effective for the therapeutic treatment of amebiasis, giardiasis and primary amebic meningoencephalitis (Bashyal et al, 2017). This anti-protozoan mechanism of creosote bush lignans disrupts the modulation of cysteine protease activity in the trophozoites, thereby reducing their virulence (Bashyal et al, 2017). Information on the effect of creosote bush biomass components on nonpathogenic rumen protozoa is non-existent, but the anti-protozoan mechanism may be similar to that described for pathogenic protozoa in humans.…”
Section: Resultados Y Discusiónmentioning
confidence: 99%
See 3 more Smart Citations
“…In intestinal protozoa (Giardia lambia, Entamoeba histolytica and Naeglia fowleri) of considerable pathogenicity to humans, secondary metabolites of creosote matter were shown to be effective for the therapeutic treatment of amebiasis, giardiasis and primary amebic meningoencephalitis (Bashyal et al, 2017). This anti-protozoan mechanism of creosote bush lignans disrupts the modulation of cysteine protease activity in the trophozoites, thereby reducing their virulence (Bashyal et al, 2017). Information on the effect of creosote bush biomass components on nonpathogenic rumen protozoa is non-existent, but the anti-protozoan mechanism may be similar to that described for pathogenic protozoa in humans.…”
Section: Resultados Y Discusiónmentioning
confidence: 99%
“…Extractos diclorometanólicos de biomasa de gobernadora mostraron actividad contra protozoos patógenos causantes de tripanosomiasis, leishmaniasis y plasmodiosis (Schmidt et al, 2012). En protozoos intestinales (Giardia lambia, Entamoeba histolytica y Naeglia fowleri) de patogenicidad considerable para humanos, los metabolitos secundarios de materia de gobernadora mostraron ser eficaces para el tratamiento terapéutico de amebiasis, giardiasis y de meningoencefalitis amebiana primaria (Bashyal et al, 2017). Este mecanismo anti protozoario de los Table 3.…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…In addition, it is an important plant with a long history of medicinal use [13]. L. tridentata contains a series of lignans, flavonoids, condensed tannins, triterpene saponins, and naphtha quinones with antimicrobial, antioxidant, and antitumor activities [14]. Several studies have reported its ability to rejuvenate injured skin, wounds, and burned skin [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%